2019
DOI: 10.1016/j.bbmt.2019.05.020
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Viral Infections after Antithymocyte Globulin–Based Conditioning in Adults Undergoing Allogeneic Hematopoietic Stem Cell Transplantation

Abstract: Antithymocyte globulin (ATG) has been shown to reduce the incidence of graft-versus-host-disease (GVHD) after matched related donor (MRD) and matched unrelated donor (MUD) hematopoietic stem cell transplantation (HCT); however, because of increased risks of infection and relapse, this use has not translated into a significant improvement in post-transplant survival. The goal of this single-center, retrospective cohort analysis was to quantify the incidence of viral reactivation and viral end-organ disease (EOD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 30 publications
2
9
0
Order By: Relevance
“…Many diseases could result in attenuated host antiviral ability. For example, it has been reported that patients receiving HSC transplantation (HSCT) are more susceptible to viruses [36‐38]. Interestingly, we found that BRCC36 expression was significantly downregulated in the allo‐HSCT disease model.…”
Section: Discussionmentioning
confidence: 63%
See 1 more Smart Citation
“…Many diseases could result in attenuated host antiviral ability. For example, it has been reported that patients receiving HSC transplantation (HSCT) are more susceptible to viruses [36‐38]. Interestingly, we found that BRCC36 expression was significantly downregulated in the allo‐HSCT disease model.…”
Section: Discussionmentioning
confidence: 63%
“…After studying several models of human diseases, we noticed that BRCC36 expression could be largely downregulated during allogeneic HSC transplantation (allo‐HSCT), as compared with syngeneic HSCT (syn‐HSCT). Clinically, patients receiving allo‐HSCT are at high risk of viral infection [36‐38]. Thus, we questioned whether BRCC36 is one of the possible regulators that result in the fact that the patients after transplantation are more susceptible to viruses.…”
Section: Resultsmentioning
confidence: 99%
“…A recent study including adult patients revealed that the use of ATG in conditioning resulted in virus-associated morbidity and mortality. 26 A higher percentage of patients who received ATG experienced virus-associated end-organ disease by day +100 when compared to patients who did not. In this study, the most common viral infections were CMV and EBV, however, some patients experienced AdV infection.…”
Section: Ad Withoutmentioning
confidence: 99%
“…Patients who receive ATG are at significantly higher risk of DNA viral reactivation. 96 In most centers, weekly surveillance is conducted for both EBV and CMV using PCR assays. In many of these patients, prophylactic letermovir has been successfully used to reduce the risk of CMV infection.…”
Section: Serotherapiesmentioning
confidence: 99%
“…Practice varies worldwide, with many American centers avoiding the use of ATG due to concerns about toxicity (particularly infectious), with increased use in Europe and Canada. Patients who receive ATG are at significantly higher risk of DNA viral reactivation 96 . In most centers, weekly surveillance is conducted for both EBV and CMV using PCR assays.…”
Section: Introductionmentioning
confidence: 99%